Pengembangan Evaluasi Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Pada Siswa Kelas VII SMP Kristen 2 Salatiga Tahun 2015/2016 - Putra, Aditya Pratama; , Prof. Dr. Sutama, M.Pd (2016)
Evaluation of learning is inseparable from the tearning process and become something very important. To obtain the optimal evaluation of mathematics learning, will be the development of evaluation of mathematics learning in curriculum 2013 based on Lesson Study. Research and development aims to 1) Analyze and describe the evaluation of mathematics learning is done by junior school teachers in SMP Kristen 2 Salatiga, 2) Set the development of an evaluation of mathematics learning in curriculum 2013 based on Lesson Study in the seventh grade SMP Kristen 2 Salatiga, and 3) analyze and test the effectiveness of the evaluation of mathematics learning in curriculum 2013 based on Lesson Study which is developed.This type of research and development is the Research and Development (R & D) with evaluative design. Data collection techniques used were interviews, observation, documentation, and testing as well as Focus Group Discussion (FGD). Technique authenticity of data checked through triangulation of sources and triangulation techniques. Qualitative data analysis techniques uses flow analysis and comparative method.The results of research and development are 1) Evaluation of mathematics learning is done by junior school teachers in Salatiga using observation, self-assessment, assessment peers, journals, tests, assignments, performance evaluation, project evaluation and portfolio, 2) Development of evaluation of mathematics learning in curriculum 2013 based on Lesson Study in the seventh class junior school in Salatiga performed on assessment instruments in affective, cognitive and psychomotor, and 3) Effectiveness of evaluation of mathematics learning in curriculum 2013 based on Lesson Study has increased for the better, from the aspect of students' involvement in tasks, aspects of the willingness of students to prepare progress reports obtained and completeness aspects of student achievement.